Perspektif Pengembangan Sumberdaya Air yang Berkelanjutan dalam Tataan Proses Transformasi Pembangunan Pertanian Subsisten Menuju Pertanian Berorientasi Industri - Sahid Susanto (agriTECH, 1998)
Water resources development is one of the key factors in the agricultural process production. Considering that water resource as a part of natural water circulates dynamically in the frame of natural law, transformation of subsistence agriculture to agro-based industry substantively affects water resources development. From this trend was then used to route the hydrology and water resources development for agricultural process production. At the operational level, the interlinked dimensions of sustainable of water resources development can be recognized economic, environmental, social and cultural. For water resources development to be sustainable in the long-term there is a need to be balance those four dimensions. In steering toward such transformation of subsistence agriculture to agro-based industry, the sustainability of water resources development to economic development in a macro scale must be linked